Investigating efl learners' speaking achievement taught by modified role play at English speaking class - Siti Farhana; Flora Flora; Muhammad Sukirlan (Aksara: Jurnal Bahasa dan Sastra, 2021)
This study seeks to find out the effect of modified role play on students’ speaking achievement. There were 28 students involved in the research. The sample consisted of two classes which one group was taken to be experimental and the other to be a control group. The data obtained through the test were analyzed by using statistical analysis. The data were collected using pre and post-test. The pretest was administered at the start of the treatment, and again after 3 meetings of modified Role Play. In conducting the research, the researcher used a speaking test rubric to evaluate the students’ speaking performance which covered five components of speaking, such as fluency, grammar, vocabulary, pronunciation, and comprehensibility. The results showed that there was a significant difference between the pre-test and the post-test scores of modified the role-play and compared to the original role play. The findings indicated that the students in the modified role-play had performed better in the post-test compared to the pre-test oral communication skills classes.